The Effectiveness of Health Education Using Truth or Dare Cards on Motivation to Maintain Female Reproductive Health at SMKN 14 Samarinda - Kamiliya, Nurjihan; Pramono, Joko Sapto; Ardyanti, Dian (Panakeia Journal of Epidemiology, 2025)
The lack of personal hygiene habits among adolescent girls can increase the risk of various health problems, particularly those related to the female reproductive system, such as cervical cancer. According to data from the Global Cancer Observatory (2022), there were 662,301 cases of cervical cancer worldwide (14.1%), with 348,874 deaths or approximately 7.1%. This study aims to analyze the effectiveness of the Truth or Dare card media in increasing the motivation of female students at SMKN 14 Samarinda to maintain reproductive health. This research employed a pre-experimental method with a One Group Pretest-Posttest design. A total of 67 students were selected using total sampling. Data analysis using the Wilcoxon test showed an increase in the percentage of students with high motivation from 69.8% to 100%, and positive attitudes from 73% to 96.8% after the intervention. The Truth or Dare card media proved effective in enhancing motivation to maintain reproductive health, with a significance value of ρ = 0.000. It can be concluded that this media positively influences the motivation of female students at SMKN 14 Samarinda.